2003
DOI: 10.1590/s1519-69842003000100004
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive ecology of a neotropical cichlid fish, Cichla monoculus (Osteichthyes: Cichlidae)

Abstract: The reproductive ecology of the freshwater fish Cichla monoculus Spix, 1831 (Osteichthyes: Cichlidae) was investigated in the Campo Grande Reservoir, Northeast Brazil. Rainfall, temperature, pH, dissolved oxygen and electrical conductivity of the water were recorded monthly. Fish collected on a monthly basis were measured, weighted, dissected, sexed and the stage of maturation of the gonads were assessed by macro and microscopic means. The semi-arid study region has short spells of rain of 2-3 months duration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
40
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 6 publications
8
40
0
4
Order By: Relevance
“…The length distributions were different for the males and females, with the former reaching greater lengths than the latter. The same has been reported for other species of Cichla (Fontenele, 1950;Lowe-McConnell, 1969;Taphorn and Duque, 1996;Câmara et al, 2002;Chellappa et al, 2003;Gomiero and Braga, 2003a;2003b;Muñoz et al, 2006). On the other hand, no differences in length were found between the sexes for Cichla temensis (Humboldt, 1821), Cichla orinocensis (Humboldt, 1821) and Cichla intermedia (Machado-Allison, 1971) in Venezuela (Jepsen et al, 1999).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The length distributions were different for the males and females, with the former reaching greater lengths than the latter. The same has been reported for other species of Cichla (Fontenele, 1950;Lowe-McConnell, 1969;Taphorn and Duque, 1996;Câmara et al, 2002;Chellappa et al, 2003;Gomiero and Braga, 2003a;2003b;Muñoz et al, 2006). On the other hand, no differences in length were found between the sexes for Cichla temensis (Humboldt, 1821), Cichla orinocensis (Humboldt, 1821) and Cichla intermedia (Machado-Allison, 1971) in Venezuela (Jepsen et al, 1999).…”
Section: Discussionsupporting
confidence: 78%
“…The oocytes matured at a size of 428.4 µm, reaching their maximum at 2,203.2 µm. were introduced (Câmara et al, 2002;Chellappa et al, 2003;Espinola, 2005) or different in natural environments (Jepsen et al, 1997;Muñoz et al, 2006). Mortality can be unequal between the sexes (Vazzoler, 1996), causing a difference in the proportion between males and females.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in the abundance of these species over the course of the study seems to be related to the trophic depression period of the ecosystem. Our results are also in agreement with other studies of introduced species that established successfully in many reservoirs in Brazil (Santos, Rocha, & Frédou, 2010;Chellappa et al, 2003;Santos, Silva, & Viana, 2003;Novaes et al, 2004; Bennemann, Carpa, Galvez, & Shibatta, 2006;Gomes, Dias, & Branco, 2008;Stefani & Rocha, 2009) and other countries (Japsen et al, 1997;Muñoz et al, 2006). Introduced species are extremely difficult to eradicate (Britton & Orsi, 2012), but a proposal to manage and control them is necessary to minimize their potentially harmful effects on the local aquatic community.…”
Section: Discussionsupporting
confidence: 93%
“…For C. monoculus the statistical analysis showed that the species did not reproduce throughout the year, but showed a long reproductive period that was not markedly seasonal. Similar results for the species were found in other studies (Gomeira & Braga, 2004;Chellappa et al, 2003;Muñoz, Damme, & Duponchelle, 2006;Souza et al, 2008;Gomiero et al, 2009;Normando et al, 2009;Vieira, Salvador, Melo, Santos, & Bazzoli, 2009).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation